Antibody Responses to Epstein‐Barr Virus in the Preclinical Period of Rheumatoid Arthritis Suggest the Presence of Increased Viral Reactivation Cycles. Issue 4 (13th February 2022) - Fechtner, Sabrina; Berens, Heather; Bemis, Elizabeth; Johnson, Rachel L.; Guthridge, Carla J.; Carlson, Nichole E.; Demoruelle, M. Kristen; Harley, John B.; Edison, Jess D.; Norris, Jill A.; Robinson, William H.; Deane, Kevin D.; et al.
Abstract : Objective: Patients with established rheumatoid arthritis (RA) demonstrate altered immune responses to Epstein‐Barr virus (EBV), but the presence and roles of EBV have not been fully explored during the pre–clinical disease period. This study was undertaken to determine if EBV infection, as evidenced by an altered anti‐EBV antibody response, either plays an important role in driving the development of RA or is a result of expanded RA‐related autoimmunity. Methods: A total of 83 subjects with RA according to the 1987 American College of Rheumatology (ACR) criteria and 83 age‐, sex‐, and race‐matched control subjects without RA were included in our study. We collected sera from RA subjects and matched controls during the pre–RA and post–RA diagnosis periods and tested the sera for the presence of 5 anti‐EBV antibodies (anti–EBV nuclear antigen 1 IgG isotype, anti–viral capsid antigen [anti‐VCA] isotypes IgG and IgA, and anti–early antigen [EA] isotypes IgG and IgA), 7 RA‐related autoantibodies (rheumatoid factor measured by nephelometry [RF‐Neph] as well as isotype‐specific IgA‐RF, IgM‐RF, and IgG‐RF, and anti–cyclic citrullinated peptide [anti‐CCP] antibodies, including anti‐CCP2, anti‐CCP3, and anti‐CCP3.1), 22 cytokines/chemokines, 36 individual anti–citrullinated protein antibodies, and IgG–cytomegalovirus (CMV) antibodies. Random forest classification, mixed modeling, and joint mixed modeling were used to determine differences in anti‐EBV antibody levels between RA subjects and controls. Results: Random forest analysis identified the presence of preclinical EBV antibodies in the serum that differentiated RA subjects from controls without RA. Specifically, IgG‐EA antibody levels were higher in RA subjects (mean ± SD 0.82 ± 0.72 international standardized ratio [ISR]) compared to controls (mean ± SD 0.49 ± 0.28 ISR). In subjects with RA, elevated serum IgG‐EA levels in the preclinical period before seroconversion were significantly correlated with increased serum IgM‐RF levels ( P  = 0.007), whereas this correlation was not seen in control subjects without RA ( P  = 0.15). IgG‐CMV antibody levels did not differ between groups. Conclusion: Subjects whose serum IgG‐EA antibody levels are elevated in the preclinical period will eventually develop RA, which suggests that EBV reactivation cycles are increased during the preclinical period of RA. A combination of RF and EBV reactivation may play an important role in the development of RA.